Legal Certainty of the Commission System in TikTok Content Monetization: A Contemporary Business Law Review - Nurhotia Harahap; Nurhalima Hasibuan (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
The transformation of the digital economy has encouraged the development of the creator economy which has made TikTok one of the main platforms for content monetization through the commission system (TikTok Affiliate). Although it provides great economic opportunities for content creators and business actors, the practice still faces problems of legal certainty, especially related to the legal relationship between the parties, transparency of the commission mechanism, changes to platform policies, and the protection of the economic rights of creators. This study aims to analyze the legal certainty of the commission system in monetizing TikTok content based on the perspective of contemporary business law enriched by the analysis of Sharia Economic Law. The research uses normative juridical methods with legislative, conceptual, and analytical approaches. Legal materials include the Civil Code, Law Number 1 of 2024 concerning Electronic Information and Transactions, the Consumer Protection Law, Government Regulation Number 71 of 2019, the DSN-MUI Fatwa regarding ju'ālah, samsarah, and wakālah bi al-ujrah contracts, as well as various related literature. The results of the study show that the commission system on TikTok Affiliate is a legally valid contractual relationship based on electronic contracts, but its implementation does not fully reflect legal certainty because there is still a lack of algorithm transparency, unilateral policy changes, an imbalance in bargaining positions, and weak dispute resolution mechanisms. Viewed from the perspective of contemporary business law, the commission system on digital platforms is allowed as long as it meets the principles of contract clarity, fairness, transparency, and avoidance of gharar elements. Therefore, adaptive regulations are needed that harmonize positive laws with sharia principles to strengthen legal certainty, protection of creators' economic rights, and accountable digital platform governance.